1 - Surpassing the Spectre of Impossibility: Ideational Impoverishment and the Quest for Sustainable Rural Learning Ecologies in Africa: par Ato Kwamena Onoma - Onoma, Ato Kwamena (Journal of Higher Education in Africa, 2022)
The idea of sustainable rural learning ecologies in Africa apparently consti- tutes a contradiction in terms. Renowned for its provincialism, rural Africa seems to represent the opposite of the ideal setting for sustainable learning ecologies, which cultivate open, questioning and investigative spirits while fostering the acquisition of knowledge and skills. This rural landscape that is often seen as the den of parochialism is the outcome of colonial and postcolonial policies and processes of ideational impoverishment; the contrived nature of what we have come to see as the rural open space for creating and perpetuating sustainable rural learning ecologies. Pursued as a forward-looking project, the deliberate creation of sustainable rural learning ecologies is warranted by peculiarities that position rural spheres as ideal domains for cutting-edge learning on some of the most important questions in an Africa undergoing rapid transformation.